2016
DOI: 10.1080/10538712.2015.1108945
|View full text |Cite
|
Sign up to set email alerts
|

I Knew It All Along: The Sexual Grooming Behaviors of Child Molesters and the Hindsight Bias

Abstract: Recent high profile cases of child sexual abuse have increased interest in the grooming behaviors of child molesters and why these offenders are not identified sooner. This study examined one possible explanation--the hindsight bias. Five hundred and twenty-six undergraduates were randomly assigned to read one of six vignettes and asked to rate the likelihood the person in the story is a child molester. Results supported the presence of the hindsight bias, with participants who were given outcome information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
2
16
2
1
Order By: Relevance
“…As Gillespie (2004) stated, grooming is “a transient feature that is difficult to capture and virtually impossible to decide when it begins and ends” (p. 586). It is usually a long-term rapport-building process that is planned (Winters & Jeglic, 2016) and takes place before initiating sexual contact (see I. A. Elliott, 2017; Leclerc, Proulx, & Beauregard, 2009).…”
mentioning
confidence: 99%
“…As Gillespie (2004) stated, grooming is “a transient feature that is difficult to capture and virtually impossible to decide when it begins and ends” (p. 586). It is usually a long-term rapport-building process that is planned (Winters & Jeglic, 2016) and takes place before initiating sexual contact (see I. A. Elliott, 2017; Leclerc, Proulx, & Beauregard, 2009).…”
mentioning
confidence: 99%
“…The literature provides a significant amount of information about the background and motivations of sexual offenders. [314][315][316][317] The research suggests that most sex offenders share similar backgrounds, similar life experiences, similar psychological problems, and similar nonsexual motivations. It is important to always identify the offender's specific motivations, many of which are nonsexual in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Past literature has suggested that these covert behaviors are not easily identified before the abuse occurs (Craven et al 2006), yet the only empirical study to date suggests that in fact participants were able to identify sexual grooming, in particular behaviors involving physical touch and isolation (Winters and Jeglic 2016). However, it has yet to be determined whether individuals are better able to recognize certain stages of the grooming process (i.e., victim selection, gaining access, trust development, and desensitization to touch).…”
Section: The Current Studymentioning
confidence: 99%
“…Therefore, the primary goal of the present study is to further examine whether grooming behaviors are recognized, and if so, which stages of the grooming process are most recognized of being indicative of future sexual abuse. Based on the findings from Winters and Jeglic (2016), it is hypothesized that participants will be able to recognize sexual grooming behaviors, in particular the stages involving gaining access and physical touch as compared to the stages of victim selection and trust development. This research is a preliminary step in gaining a better understanding of perceptions of grooming behaviors of predatory sexual offenders.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation